Exploring Student Perceptions of Teaching Strategies in Business English Courses: Insights from EFL Contexts - Dahlan, Suratman; Ramdani, Amaliah; Noni, Nurdin (Inspiring: English Education Journal, 2024)
The aims of this research were exploring the teaching strategies used by lecturers in Business English courses in Universitas Khairun, Ternate within the EFL context. The researchers used classroom observation and semi structure interview to collect the data. There were two lecturers and two classes of students who participated in this study. The findings of this research reveal that the case method and project-based learning (PBL) were the most commonly used strategies, while cooperative learning, small group work, and direct teaching were also occasionally applied. Although these strategies were effective in enhancing students’ understanding of business concepts, they did not significantly contribute to the improvement of students’ English language proficiency.